PENGARUH PEMBERIAN BERBAGAI JENIS PESTISIDA NABATI TERHADAP TANAMAN SELADA VARIETAS SIOMAK (Lactuca sativa L.) - Khufrotun Naharwati; Umi Barokah (Yayasan Nusantara Hasana Berdikari, 2025)
Lettuce is a vegetable that is well known among the Indonesian people and comes in various varieties, one of which is the siomak variety that contains 8 mg of vitamin C (Haryani, 2018). This study aims to determine the effect of several types of plant-based pesticides on the growth of siomak lettuce and to identify the best treatment. The research was conducted in Sidobunder Village, Puring District, Kebumen Regency, using a Completely Randomized Design (CRD) without factorial. The treatments consisted of W0 (no treatment), W1 (papaya leaf plant pesticide), W2 (neem leaf plant pesticide), W3 (garlic plant pesticide), W4 (tobacco leaf plant pesticide), and W5 (castor bean leaf plant pesticide). Applications were made twice a week, specifically in the 1st and 4th weeks. Each treatment was repeated four times with each plot containing 16 plants. The observed data were analyzed using SPSS software through ANOVA, followed by a DMRT test at a significance level of 5% to determine the differences between treatments and the most effective treatment. The results obtained showed that the plant pesticide had a significant effect on plant height, the number of leaves, and the intensity of pest attacks. The best treatment was found to be the neem leaf plant pesticide with a plant height of 51.3725 cm, a number of leaves of 15.25 cm, and the lowest intensity of pest attacks at 0.0879.